Influence of Arm Muscle Strength and Concentration on Badminton Long Service Ability in Elementary Schools - Rajab, Abd; Fahrizal, Fahrizal; Kamaruddin, Ilham; Adil, Ahmad; Hudain, Muh. Adnan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study intends to analyze the effect of arm muscle strength, eye-hand coordination, and concentration on badminton long serving ability in students. This type of research uses a quantitative approach with a correlational design. The sample of this study at elementary school YPS Lawewu Sorowako amounted to 16 students. We measured arm strength using a hand-grip dynamometer and evaluated eye-hand coordination through a ball wall-toss test. We analyzed the data using SPSS and AMOS for path analysis. The results indicated that there was a weak positive effect between arm muscle strength and long serve. This effect was not statistically significant because the significance value (0.566) was much greater than 0.05. There was a weak positive effect between eye-hand coordination and long serve. This effect was not statistically significant because the significance value (0.423) was greater than 0.05. There was a weak negative effect between concentration and long service. The effect is not statistically significant because the significance value (0.212) is greater than 0.05. Additionally, there is no significant effect of both variables on long service. Both variables have a significance value > 0.05. Concentration has a negative effect (-0.417). Hand-eye coordination has a weak positive effect (0.152). The conclusion is that there is a weak positive effect between arm muscle strength, hand-eye coordination, and badminton long service. There is a weak negative effect of concentration on badminton long service performance. Next, there is no significant effect of arm muscle strength or hand-eye coordination through concentration on the badminton long service ability of Elementary School extracurricular participants.